Computer-assisted preoperative simulation for positioning and fixation of plate in 2-stage procedure combining maxillary advancement by distraction technique and mandibular setback surgery. (2016) - Suenaga, Hideyuki; Taniguchi, Asako; Yonenaga, Kazumichi; Hoshi, Kazuto; Takato, Tsuyoshi
Highlights: Reported a case of maxillary retrusion by a bilateral cleft lip and palate. Preoperative simulation was performed for positioning and fixation of plate. Maxillary advancement by distraction technique and mandibular setback surgery. 2-stage procedure with maxillary advancement was found to be accurate. Abstract: Introduction: Computer-assisted preoperative simulation surgery is employed to plan and interact with the 3D images during the orthognathic procedure. It is useful for positioning and fixation of maxilla by a plate. We report a case of maxillary retrusion by a bilateral cleft lip and palate, in which a 2-stage orthognathic procedure (maxillary advancement by distraction technique and mandibular setback surgery) was performed following a computer-assisted preoperative simulation planning to achieve the positioning and fixation of the plate. A high accuracy was achieved in the present case. Presentation of case: A 21-year-old male patient presented to our department with a complaint of maxillary retrusion following bilateral cleft lip and palate. Computer-assisted preoperative simulation with 2-stage orthognathic procedure using distraction technique and mandibular setback surgery was planned. Discussion: The preoperative planning of the procedure resulted in good aesthetic outcomes. The error of the maxillary position was less than 1 mm. Conclusion: The implementation of the computer-assisted preoperative simulation for the positioning and fixation of plate in 2-stage orthognathic procedure using distraction technique and mandibular setback surgery yielded good results.